STORYTELLING DAN MAKNA PADA IKLAN FIAT 500 - Wahyu Indira (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
Advertising activities have existed since the Greek and Roman times through verbal communication. In modern times advertising activities are practiced almost every time by large companies through mass media. These companies are willing to spend millions of dollars searching a way to create unique and creative ways to advertise. Besides advertisement must have an attractive appearance, the ad must also give a meorable impression that are easy to remember. One way to make ads easy to remember is to insert a story behind the visuals of the ad. Fiat is an Italian automotive company that inserts storytelling in Fiat 500 series adverts. With the brilliant minds of Dave Hill and his digital processing capabilities Fiat is able to produce a unique and interesting ad with the dual meaning of denotative and connotative through story.